CLINICOPATHOLOGICAL STUDY OF UTERINE LEIOMYOMA WITH VARIOUS ASSOCIATED PATHOLOGIES IN A TERITIARY CARE CENTER. - RAJITHA, JILLA; SUMALATHA, KASTHURI; SEKHAR R, PANDI INDRA; GANGADHAR BIRADAR, RUTUSHRI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The present study was conducted to find the clinicopathological features of uterine leiomyoma seen in hysterectomy and myomectomy specimens. Methods: A 2-year retrospective study was done from January 2021 to December 2022 at Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar. 100 patients diagnosed with leiomyoma on histopathological examination of hysterectomy specimens were included in the study. Results: Uterine leiomyoma was most common in women in the age group of 41–50 years (80%) and presented with abdominal pain (60%). The most common location was intramural (40%), and the most common degeneration was a hyaline change (18%). Conclusion: The benign tumor of smooth muscle, uterine leiomyoma, is commonly seen in perimenopausal females. Leiomyoma is associated with various pathologies, comprising degenerative changes and coexisting benign and malignant lesions. Hence, histopathological examination should be done to identify the spectrum of uterine leiomyoma and associated pathologies.